2009
DOI: 10.1530/rep-08-0503
|View full text |Cite
|
Sign up to set email alerts
|

Spermatozoal transcriptome profiling for bull sperm motility: a potential tool to evaluate semen quality

Abstract: Regarding bull fertility, establishing an association between in vitro findings and field fertility requires a multi-parametric approach that measures the integrity of various structures and dynamic functions, such as motion characteristics, among others. The heterogeneous RNA pattern of spermatozoa could be used in genomic analysis for evaluating both spermatogenesis and fertility potential of semen, mainly because of the static status of the transcriptome of this particular differentiated cell. In a previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 46 publications
4
86
0
3
Order By: Relevance
“…Furthermore, the expression level of let-7a in human seminal plasma was significantly associated with male infertility (Wu et al 2012). Studies have shown that both miR-26a and miR10b, which are also present in mouse and bull sperms (Amanai et al 2006, Bissonnette et al 2009), appear to be associated with carcinogenesis (Ma et al 2007, Kato et al 2015, but their role in spermatogenesis and in early embryonic development remains unknown. The functional significance of most other miRNAs remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the expression level of let-7a in human seminal plasma was significantly associated with male infertility (Wu et al 2012). Studies have shown that both miR-26a and miR10b, which are also present in mouse and bull sperms (Amanai et al 2006, Bissonnette et al 2009), appear to be associated with carcinogenesis (Ma et al 2007, Kato et al 2015, but their role in spermatogenesis and in early embryonic development remains unknown. The functional significance of most other miRNAs remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the functions of the majority of the sperm mRNAs remain enigmatic, it has been proposed that sperm mRNAs may play roles in the regulation of sperm morphology, motility and capacitation and that sperm transcriptional profiles might provide clinical markers for male fertility (Lambard et al 2004, Li et al 2007, Bansal et al 2015. Similarly, sperm transcriptome studies have been initiated in bulls and have revealed the differences between the mRNA profiles of high-and low-fertility males (Lalancette et al 2008, Bissonnette et al 2009. Recently, the spermborne mRNA Wnt4 was found to be delivered into the fertilized oocyte and translated, which represents evidence of a paternal effect on zygotic development (Fang et al 2014); however, the functional significance of sperm mRNAs in the development of zygotes remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jasko et al (1990a) and findings provided a better concept of the biological importance of sperm RNAs, allowing the identification of biomarkers of stallion fertility. The sperm transcriptome has been studied in humans (Ostermeier et al 2002), boars (Kempisty et al 2008;Yang et al 2009) and bulls (Gilbert et al 2007;Bissonnette et al 2009;Feugang et al 2010), and the utility of sperm RNA as a marker of infertility has been explored (Miller 2000;Steger 2001), whereby differences in transcript levels in spermatozoa with different motilities (Bissonnette et al 2009;Lambard et al 2004), as well as between normal and abnormal sperm samples (Platts et al 2007;Steger et al 2003), have been reported. Krawetz (2005) demonstrated that some of the sperm RNAs can be delivered to the oocyte during fertilisation.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse mRNAs have been found in human, rodent and bovine mature spermatozoa (Dadoune et al, 2005;Gilbert et al, 2007;Miller and Ostermeier, 2006a). Although the roles of these transcripts during embryonic and fetal development are still unclear, analysis of their profiles could serve as a diagnostic tool to assess male infertility (Bissonnette et al, 2009;Garrido et al, 2009;Lalancette et al, 2009), or it could have prognostic value for fertilization and embryo development (Boerke et al, 2007;Ostermeier et al, 2004;Sassone-Corsi, 2002).…”
Section: Mrnas Of Spermatozoamentioning
confidence: 99%